Der Jahresgang des mittleren geographischen Höhengradienten der Lufttemperatur in den verschiedenen Klimagebieten der Erde - Lautensach, Hermann; Bögel, Robert (ERDKUNDE, 1956)
The average vertical gradient of air temperature, like all other climatic elements, shows a variation throughout the year, its course running differendly in the different climatic regions of the world. An investigation of this feature was suggested by H. Lautensach and carried out by R. Bögel, who made use of the data of 297 pairs of terrestrial weather Stations on mountains throughout the world. Because of the all too great distance between two stations of a pair, auxiliary stations had frequently to be used. Wherever possible observation data of the free atmosphere were used for comparison. Nine types of annual variation of the vertical temperature gradient were found. Middle Europe is governed by the normal type where the maximum occurs in summer and the minimum during the winter. In the regions of subtropical climate with dry summers (Köppen’s Cs climate) the Cs-Type, showing a summer minimum and a winter maximum, prevails. The type of the poles of coldness is characterised by negative values of the vertical temperature gradient, i. e. an increase of the monthly mean temperature with altitude. The origin and distribution of these types is explained by reference to the respective different properties of the base layer of the troposphere as they have become known from the investigations of Schneider-Carius in 1953. Since the average vertical gradient, regionally as well as seasonally, is subject to pronounced variations which, according to the data used, lie between + 1.16° C and - 1.84° C per 100 m., it will no longer be permissible to reduce mean temperatures to sea level everywhere and for every month simply by means of the usual amount of 0.5° C per 100 m. Rather is it necessary to differentiate the reduction factor regionally as well as seasonally, and the reduction of the annual variations of the monthly temperature to sea level must also be clone accordingly.